Structure and physiological function of the human KCNQ1 channel voltage sensor intermediate state - Keenan C Taylor; Po Wei Kang; Panpan Hou; Nien-Du Yang; Georg Kuenze; Jarrod A Smith; Jingyi Shi; Hui Huang; Kelli McFarland White; Dungeng Peng; Alfred L George; Jens Meiler; et al. (eLife, 2020)
Voltage-gated ion channels feature voltage sensor domains (VSDs) that exist in three distinct conformations during activation: resting, intermediate, and activated. Experimental determination of the structure of a potassium channel VSD in the intermediate state has previously proven elusive. Here, we report and validate the experimental three-dimensional structure of the human KCNQ1 voltage-gated potassium channel VSD in the intermediate state. We also used mutagenesis and electrophysiology in Xenopus laevisoocytes to functionally map the determinants of S4 helix motion during voltage-dependent transition from the intermediate to the activated state. Finally, the physiological relevance of the intermediate state KCNQ1 conductance is demonstrated using voltage-clamp fluorometry. This work illuminates the structure of the VSD intermediate state and demonstrates that intermediate state conductivity contributes to the unusual versatility of KCNQ1, which can function either as the slow delayed rectifier current (IKs) of the cardiac action potential or as a constitutively active epithelial leak current.